Copyright Payments in Eighteenth-Century Britain, 1701–1800. (16th March 2017) - Fielding, David; Rogers, Shef
Abstract : Drawing on published references to copyright payments made to authors between 1701 and 1800, this article matches each payment to the published book and calculates the value of payments to authors relative to the number of sheets each copy required and correlated to the sale price for the book. Although a relatively small sample of just over 400 titles, the study shows that entertainment was generally more rewarding for authors than history, philosophy and sermons, while booksellers made good returns on practical and informative works. Booksellers' valuations of works align surprisingly well with subsequent critical assessments of the quality of the works, indicating a high degree of discrimination and taste within the booktrade. The full spreadsheet of data for the study is freely available online at https://goo.gl/TzQnYO .